Research in administrative sciences under COVID-19 - Limón, Mónica Lorena Sánchez; García, María Luisa Saavedra (Emerald Publishing Limited, 2022)
Due to the COVID-19 pandemic the entire world experienced a health, humanitarian, and economic crisis with no record in the present century, leading to the paralysis of activities by voluntary or mandatory quarantines. There is great uncertainty about how long the crisis will last and how recovery will be achieved, because of this paralysis and the contraction of demand, auguring a slow recovery. Research in Administrative Sciences under COVID-19 examines the context surrounding organizations in the face of the COVID-19 Pandemic. Detailing various aspects related to companies and their competitiveness in the face of the global health crisis, chapters cover topics on intellectual capital, burnout (professional exhaustion), stress and technostress, as well as pandemic effects on the human capital of organizations. Developing upon the issues of Corporate Social Responsibility, E-commerce in times of COVID-19 and Design Thinking as a strategy for the economic reactivation of start-ups in Mexico, this volume is the result of research efforts carried out by 23 outstanding researchers from 12 Mexican and Latin American higher education institutions.